Co-suspension delivery technology in pressurized metered-dose inhalers for multi-drug dosing in the treatment of respiratory diseases. (January 2018) - Ferguson, Gary T.; Hickey, Anthony J.; Dwivedi, Sarvajna
Abstract: Technologies for long-term delivery of aerosol medications in asthma and chronic obstructive pulmonary disease have improved over the past 2 decades with advancements in our understanding of the physical chemistry of aerosol formulations, device engineering, aerosol physics, and pulmonary biology. However, substantial challenges remain when a patient is required to use multiple inhaler types, multiple medications, and/or combinations of medications. Combining multiple drugs into a single inhaler while retaining appropriate dosing of the individual agents in the combination may enhance patient adherence to therapy and reduce device errors that occur when patients are using multiple inhalers. Pressurized metered-dose inhaler (pMDI) devices are widely used by patients for acute symptom relief as well as maintenance treatment, so the pMDI may be a suitable option with which to explore medication combinations. However, optimizing drug formulation remains a key challenge for pMDI delivery systems. This article introduces a new pMDI formulation approach: co-suspension delivery technology, which uses drug crystals with porous, low-density phospholipid particles engineered to deliver combinations of drugs to the airways with accurate and consistent dosing via pMDIs, independent of medication types and combinations. We describe the key characteristics of pMDIs, and discuss the rationale for the co-suspension delivery technology platform based on the limitations associated with traditional formulations. Finally, we discuss the clinical implications of co-suspension delivery technology for developing combination drug therapies administered by pMDIs. Highlights: pMDIs are one of many inhaler devices used to deliver asthma and COPD medication. Co-suspension delivery technology is a novel formulation for pMDI inhaler devices. This technology delivers uniform doses and ensures suspension stability. It allows multiple drugs with variable characteristics to be combined in one pMDI. Use of a single device may facilitate drug development and improve adherence.